Spectrum of male breast lesions: an institutional perspective - Ganguly, Siyum; Sheikh, Shah Alam; Phukan, Angela; Das, Jahnabi; Das, Surjya Sekhar (International Journal of Medical Research and Review, 2016)
Background: Fine needle aspiration is a quick and effective method in the diagnosis of breast lumps and is being widely used in the preoperative assessment of breast lesions. Studies related to male breast lesions are rare. The aim of our study is to study the spectrum of male breast lesions and to analyze the cytological spectrums of these lesions. Materials and Methods: The study was conducted over a period of 5 years. FNAC was done on all male patients clinically presenting with breast lesions. Cytological findings were retrospectively correlated with histopathological dignosis. FNAC diagnosis was categorized as benign, malignant, suspicious of malignancy and unsatisfactory. Results: Male breast lesions formed 6.2% (38 cases) of the 612 breast lesions which were sent for FNA over a period of 5 years. Of these histopathological examination was done only in 19 cases. 86.8% (33 cases) were benign or reactive and 10.6% (4 cases) were malignant. Gynecomastia was the commonest benign lesion (29 cases). Conclusion: This study showed that FNAC is a reliable, sensitive and specific diagnostic tool for diagnosing male breast lesions. Hence, it should be used as a first line of investigation in the evaluation of male breast lesions.